2017
DOI: 10.1002/glia.23204
|View full text |Cite
|
Sign up to set email alerts
|

Siglec‐H is a microglia‐specific marker that discriminates microglia from CNS‐associated macrophages and CNS‐infiltrating monocytes

Abstract: Several types of myeloid cell are resident in the CNS. In the steady state, microglia are present in the CNS parenchyma, whereas macrophages reside in boundary regions of the CNS, such as perivascular spaces, the meninges and choroid plexus. In addition, monocytes infiltrate into the CNS parenchyma from circulation upon blood-brain barrier breakdown after CNS injury and inflammation. Although several markers, such as CD11b and ionized calcium-binding adapter molecule 1 (Iba1), are frequently used as microglial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 78 publications
2
102
0
1
Order By: Relevance
“…4b, c, red asterisk) [27,28,55]. Sialic acid-binding immunoglobulin-type lectin H (SiglecH), a specific microglia marker [56] that was suggested to be expressed when these cells are polarized toward the inflammatory phenotype, was also highly expressed by reactive microglia in our assay (Fig. 4c).…”
Section: Reactive Microglia and Infiltrating Macrophages Have Distincmentioning
confidence: 70%
“…4b, c, red asterisk) [27,28,55]. Sialic acid-binding immunoglobulin-type lectin H (SiglecH), a specific microglia marker [56] that was suggested to be expressed when these cells are polarized toward the inflammatory phenotype, was also highly expressed by reactive microglia in our assay (Fig. 4c).…”
Section: Reactive Microglia and Infiltrating Macrophages Have Distincmentioning
confidence: 70%
“…For this purpose, we per-formed a synapse engulfment assay (Schafer et al, 2012) in the mossy fiber pathway to detect the volume of synaptic elements engulfed by microglia in mice, in which microglia are selectively labeled with GFP (Zhan et al, 2014) ( Figure 3A). We confirmed that no GFP(+) cell in the hippocampal CA3 was immunopositive for CCR2 (Prinz and Priller., 2010), an infiltrating cell-specific marker ( Figure S3), while GFP(+) cells were stained with an antibody for Siglec-H (Zhang et al, 2006;Konishi et al, 2017) and P2Y12R (Sasaki et al, 2003;Haynes et al, 2006;Mildner et al, 2017), which were generally used as microglia-specific markers ( Figure S3). Furthermore, GFP(+) cells expressed interleukin-1b (IL-1b), one of the typical cytokines released from microglia (Figure S3).…”
Section: Exercise In Adulthood Stimulates Microglia To Prune Synapsesmentioning
confidence: 99%
“…In addition, CSF‐1R inhibition can robustly decline the actions of nerve‐associated macrophages in the periphery (Klein et al, ). However, several studies have identified some potential markers that are exclusively expressed in microglia including Tmem119, P2RY12, Siglec‐H and Sal1, permitting distinction of resident microglia from other myeloid cells (Bennett et al, ; Butovsky et al, ; Buttgereit et al, ; Konishi et al, ). These markers, together with the Cre/loxP technology, may make it possible to deplete microglia with exquisite precision in the near future.…”
Section: Depleting Microglia In Diseases: the Friend In Need May Notmentioning
confidence: 99%